2017
DOI: 10.3918/jsicm.24_121
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of tetanus using the herbal medicine shakuyakukanzoto: a report of three cases

Abstract: -125 - 破傷風に対する芍薬甘草湯 AbstractSuccessful treatment of tetanus using the herbal medicine shakuyakukanzoto: a report of three cases Tetanus can rapidly develop into muscle spasm accompanied by respiratory failure and result in fatal outcomes. Although the management of muscle spasticity and rigidity is of great importance, there is no consensus on the best treatment modality. Recently, the herbal medicine shakuyakukanzoto has been reported to be effective for the treatment of the muscle disorder in 2 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…There are only seven cases in which kampo medicines were used for the treatment of tetanus (Tables ,) . In all cases the patients survived, but pseudoaldosteronism occurred after the use of SKT in three of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are only seven cases in which kampo medicines were used for the treatment of tetanus (Tables ,) . In all cases the patients survived, but pseudoaldosteronism occurred after the use of SKT in three of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…In four out of seven cases, pseudo-aldosteronism, such as hypokalaemia, slight oedema, or hypertension, occurred after SKT use and all symptoms improved after its discontinuation. The daily licorice dose and the duration of licorice treatment should be carefully determined [45].…”
Section: Treatment For Tetanus Using Both Western and Kampo Medicinementioning
confidence: 99%
“…Mechanical ventilation was performed for 50 days in one case. As for Kampo formula, SKT alone was used in all five cases [45][46][47]. Nevertheless, not only shakuyakukanzoto but also other Kampo formulas such as kakkonto and daijokito may be effective for tetanus.…”
Section: Treatment For Tetanus Using Both Western and Kampo Medicinementioning
confidence: 99%
“…Shakuyakukanzoto (SKT) is one of Kampo medicines, and is clinically used for the treatment of pain associated with sudden myospasm widely. Recently, some studies showed that they are effective in treating muscle spasms caused by tetanus [12][13][14][15]. Especially, Nakae et al reported that the use of SKT reduced the dosage of propofol which was administered for the control of spastic convulsion in a tetanus patient [12].…”
Section: Introductionmentioning
confidence: 99%